2017
DOI: 10.3892/ol.2017.7278
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of telomere length to malignancy potential in non‑melanoma skin cancers

Abstract: Abstract.Telomeres are associated with cell fate and aging through their role in the cellular response to stress and growth stimulation resulting from previous cell divisions and DNA damage. Telomere shortening has been observed in most human cancers, and is known to be a feature of malignancy. The aim of this study is to clarify whether telomere length is related to the malignant potential of non-melanoma skin cancers. Telomere length was analyzed using tissue quantitative fluorescence in situ hybridization i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Using Q-FISH for the determination of TL in neoplastic epidermal cells, Yamada-Hishida et al found that TL was decreased in BD and AK (both had relatively close TL) in relation to BCC and SCC, suggesting that TL estimation in NMSC reflects its biological behavior, such as the metastatic and invasive potential. Moreover, the authors suggested that SCC precursor lesions exhibit a different TL from those of SCC [78]. On the contrary, Wainwright et al examined BCC and TL in relation to normal skin and reported that telomeres from BCC samples had a variable range of TL (out of the 20 samples they examined 13, had an increased mean TL, while 7 had a shorter TL) [79].…”
Section: Telomere Length (Tl)mentioning
confidence: 99%
“…Using Q-FISH for the determination of TL in neoplastic epidermal cells, Yamada-Hishida et al found that TL was decreased in BD and AK (both had relatively close TL) in relation to BCC and SCC, suggesting that TL estimation in NMSC reflects its biological behavior, such as the metastatic and invasive potential. Moreover, the authors suggested that SCC precursor lesions exhibit a different TL from those of SCC [78]. On the contrary, Wainwright et al examined BCC and TL in relation to normal skin and reported that telomeres from BCC samples had a variable range of TL (out of the 20 samples they examined 13, had an increased mean TL, while 7 had a shorter TL) [79].…”
Section: Telomere Length (Tl)mentioning
confidence: 99%
“…The relation of telomere length with the malignant potential of different NMSCs was analyzed in AK, BD, BCC and cSCC tumours and surroundings epidermal tissues by calculating the telomere centromere ratio (TCR), which reflects telomere length more accurately than other experimental procedures [77]. TCR values for cSCC were significantly lower than those for BD and AK (cSCC < BD < AK) and peritumoral epidermal cells had higher TCR values than tumour cells.…”
Section: Telomere and Telomerase Activity In Cutaneous Squamous Cementioning
confidence: 99%
“…TCR values for cSCC were significantly lower than those for BD and AK (cSCC < BD < AK) and peritumoral epidermal cells had higher TCR values than tumour cells. These findings demonstrated that tumour biological behaviour was intrinsically related to telomere length and that telomere shortening is consistent with the invasive progression [77].…”
Section: Telomere and Telomerase Activity In Cutaneous Squamous Cementioning
confidence: 99%
“…As a prognostic biomarker, tissue TL outperforms existing clinical risk parameters. Several studies have investigated the relationship between TL and clinical features in squamous cell carcinoma (SCC) [31][32][33]. In cancer tissues, TL is linked to risk factors for oesophageal SCC in consumers of alcohol [31] and to cytologic biomarkers for cervical cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…In cancer tissues, TL is linked to risk factors for oesophageal SCC in consumers of alcohol [31] and to cytologic biomarkers for cervical cancer [32]. Furthermore, in non-melanoma skin cancer, TL was found to be significantly lower in SCC than in basal cell carcinoma, Bowen's disease, or keratosis [33]. In summary, we have demonstrated that the tumour/normal TL ratio is abnormally low in patients with a poor prognosis, and this may be a critical event in progression of HNSCC.…”
Section: Discussionmentioning
confidence: 99%